KONTRIBUSI SENAM IBU HAMIL TRIMESTER III DALAM PENGURANGAN NYERI PINGGANG DI WILAYAH EKSKOTATIF CILACAP - Intarti, Wiwit Desi; Pusitasari, Lina (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Lower back pain in pregnancy is a clinical syndrome characterized by the main symptoms of pain or other feeling uncomfortable in the rear areas of the body from the last rib to the buttocks or anus due to the influence of the hormone. Back pain in pregnant women can lead to muscle which raises spasme pain. Spasme prolonged muscle may cause vasoconstriction of the blood vessels, it is dangerous in the mother and fetus. The purpose of the research is to find out the effectiveness of the contribution of the III trimester of pregnant women's gymnastics in the reduction of low back pain in the region of ekskotatif cilacap. Types of research: the study used is the experimental type of quantitative research, and through case-control approach. Number of population of pregnant women 140, and the number of samples is 33 pregnant women trimester III randomly selected or RCT and grouped in the Group of cases and the control group. Technique of data analysis using the Mann-Whitney test with SPSS programme 20. Conclusion of gymnastics III trimester of pregnant women contribute to the reduction of low back pain in the region of ekskotatif cilacap. Key Words: Low Back Pain, The III Trimester Pregnant, Gymnastics